Angiogenic/osteogenic response of BMMSCs on bone‐derived scaffold: Effect of hypoxia and role of PI3K/Akt‐mediated VEGF‐VEGFR pathway. Issue 7 (25th February 2014) - Zhou, Yi; Guan, Xiaoxu; Yu, Mengfei; Wang, Xinhua; Zhu, Wenyuan; Wang, Chaowei; Yu, Mengliu; Wang, Huiming
Abstract Bone tissue deficiency is a common clinical challenge. Tissue‐engineered bone constructs are an effective approach for the repair of orthopedic bone defects. Mimicking the essential components of the in vivo microenvironment is an efficient way to develop functional constructs. In this study, bone marrow‐derived mesenchymal stromal cells (BMMSCs) were seeded into bone‐derived scaffolds, a material with similar structure to natural bone. This was done under hypoxic conditions, an environment that imitates that experienced by BMMSCs in vivo. Our data indicate that hypoxia (5% O2) significantly increases the proliferation of BMMSCs seeded in scaffolds. As reflected by highly expressed osteogenesis‐ and angiogenesis‐associated biomarkers, including vascular endothelial growth factor (VEGF), RUNX2, bone morphogenetic protein‐2/4 and osteopontin, hypoxia also significantly increases the osteogenic and angiogenic responses of BMMSCs seeded into bone‐derived scaffold composites. PI3K/Akt‐mediated regulation of VEGF‐activated VEGFR1/2 signaling is important for hypoxia‐induced proliferative/osteogenic/angiogenic responses in BMMSC cellular scaffolds. The combination of bone‐derived scaffolds and hypoxia is conducive to the differentiation of BMMSCs into functional tissue‐engineered scaffold composites.